2009
DOI: 10.1002/art.24879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of teriparatide versus alendronate for treating glucocorticoid‐induced osteoporosis: Thirty‐six–month results of a randomized, double‐blind, controlled trial

Abstract: Objective. To compare the bone anabolic drug teriparatide (20 g/day) with the antiresorptive drug alendronate (10 mg/day) for treating glucocorticoidinduced osteoporosis (OP).Methods. This was a 36-month, randomized, double-blind, controlled trial in 428 subjects with OP (ages 22-89 years) who had received >5 mg/day of prednisone equivalent for >3 months preceding screening. Measures included changes in lumbar spine and hip bone mineral density (BMD), changes in bone biomarkers, fracture incidence, and safety.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
259
0
33

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 443 publications
(310 citation statements)
references
References 34 publications
18
259
0
33
Order By: Relevance
“…(2,3,55) In the clinical trials with teriparatide and PTH(1-84), no increase in nonosseous cancers was found. (20,26,29,31) However, because many tissues and solid tumors could express the PTH/PTHrP receptor, it has been suggested that patients with a history of cancers in the past 5 years avoid PTH therapy. (75) There may be wisdom in this recommendation for those whose malignancies harbor osteoblastic potential, such as breast and prostate cancer.…”
Section: Safety Of Pth In Patients With History Of Malignancymentioning
confidence: 99%
See 3 more Smart Citations
“…(2,3,55) In the clinical trials with teriparatide and PTH(1-84), no increase in nonosseous cancers was found. (20,26,29,31) However, because many tissues and solid tumors could express the PTH/PTHrP receptor, it has been suggested that patients with a history of cancers in the past 5 years avoid PTH therapy. (75) There may be wisdom in this recommendation for those whose malignancies harbor osteoblastic potential, such as breast and prostate cancer.…”
Section: Safety Of Pth In Patients With History Of Malignancymentioning
confidence: 99%
“…(20) Similar results were reported in other clinical trials, which also showed little or no incidence of hypercalcemia within 24 hours after teriparatide injection. (26,28,29,79,80) In a post hoc analysis, Miller and colleagues (81) showed a significantly higher incidence of hypercalcemia in patients with moderate renal impairment (glomerular filtration rate [GFR] 30-49 mL/min).…”
Section: Hypercalcemia and Hypercalciuriamentioning
confidence: 99%
See 2 more Smart Citations
“…Teriparatide: in a 36-month study that compared teriparatide versus alendronate in patients treated with glucocorticoids, teriparatide was more effective than alendronate in improving BMD (primary endpoint) and incidence of vertebral fractures (secondary endpoint) (38). For this reason, treatment with teriparatide is considered as a first line option for patients with glucocorticoid-induced osteoporosis and at least one previous fracture (secondary prevention) in the recent revision of the Italian AIFA Note 79.…”
mentioning
confidence: 99%